Taxonomic update, distribution and conservation status of grammitid ferns (Polypodiaceae, Polypodiopsida) in Veracruz State, Mexico - Krömer, Thorsten; Acebey, Amparo R.; Smith, Alan R. (Phytotaxa, 2013)
Grammitid ferns are a group of about 750 species, which have been treated as a distinct family (Grammitidaceae) or as part of the Polypodiaceae. Generic concepts have been in great flux, and especially in the last two decades, several new genera have been segregated on the basis of morphological and molecular data. There are 37 species of grammitids known from Mexico, of which 18 species distributed in seven genera (Alansmia, Cochlidium, Galactodenia, Melpomene, Moranopteris, Stenogrammitis, and Terpsichore) are currently known from Veracruz. Most grammitids in Veracruz and Mexico seem to be rare, and occur generally very locally in montane rain and cloud forests, which are one of the country’s most threatened ecosystems and have been widely replaced due to human activities. We provide a taxonomically updated species list for Veracruz and an evaluation of conservation status considering the IUCN regional criteria for each species, based on 132 specimens. About 72% of grammitid species from Veracruz belong to a threatened category, mainly because of a very limited number of known populations either in Los Tuxtlas or central area, whose humid montane forests have suffered major habitat destruction within the last decades or still are under severe anthropogenic pressure.